2014
DOI: 10.1007/s00405-014-3360-4
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment of idiopathic sudden sensorineural hearing loss: analysis of an RCT and material drawn from the Swedish national database

Abstract: A randomized placebo-controlled study has demonstrated no effect of prednisolone in customary dosage on idiopathic sudden sensorineural hearing loss (ISSNHL). The aim of the present paper is to analyse a larger patient group by meta-analysis of data from the RCT together with a corresponding material drawn from the Swedish national database for ISSNHL. Data from 192 patients, 18-80 years with ISSNHL, were available. All had an acute hearing loss of at least 30 dB measured as PTA in the three most affected cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In prior studies, however, multivariable statistical analysis suggested that increasing age slightly worsened the prognosis for hearing recovery (3234). Some authors have stated that the highest incidence for ISSHL is around an age of 50 years (35,36).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In prior studies, however, multivariable statistical analysis suggested that increasing age slightly worsened the prognosis for hearing recovery (3234). Some authors have stated that the highest incidence for ISSHL is around an age of 50 years (35,36).…”
Section: Discussionmentioning
confidence: 93%
“…Some studies performed multivariable statistical analysis to filter out important factors influencing the prognosis. However, we think it would help advance the field to also have individual patient data available for meta-analyses (34,5458). Even in times of continuing efforts of cost reductions for print publication, publishers need to understand the importance of providing individual patient data, at least in the form of supplementary digital materia…”
Section: Discussionmentioning
confidence: 99%
“…Systemic steroids are the standard initial treatment for ISSNHL, although a placebo-controlled study showed that systemic steroids did not result in superior improvement [11]. IT steroid injections are effective when they are used alone or with systemic steroid administration.…”
Section: Introductionmentioning
confidence: 99%
“…The three studies had contradictory findings and small sample sizes (N=267 total), and as such no recommendation could be made about the efficacy of steroids in the management of SSNHL . The authors of another meta‐analyses concluded that oral prednisolone in a standard dosing regimen does not influence recovery in SSNHL . In the literature currently, oral steroids are often used as a control when investigating new therapies, such as nonsteroidal pharmacological agents or intratympanic steroids.…”
Section: Steroidsmentioning
confidence: 99%
“…42,43 The authors of another metaanalyses concluded that oral prednisolone in a standard dosing regimen does not influence recovery in SSNHL. 44 In the literature currently, oral steroids are often used as a control when investigating new therapies, such as nonsteroidal pharmacological agents or intratympanic steroids. The most commonly used steroids in these trials are prednisone, prednisolone, and methylprednisolone.…”
Section: Systemic Steroidsmentioning
confidence: 99%